Preparation method of high-entropy material as well as product and application of high-entropy material
CoFeMnCuZn, a high-entropy material prepared by the sol-gel method, combines the photothermal effect to form an efficient catalytic layer, solving the problem of difficult removal of H2S foul odor gas in the trash can, achieving efficient room temperature catalytic oxidation, significantly reducing gas dissipation, and enhancing the environmental value and functionality of the trash can.
Patent Information
- Application Number
- CN202510032849.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The prior art is difficult to effectively remove H2S odor gases in trash cans, resulting in environmental pollution and a decline in quality of life.
The high-entropy material CoFeMnCuZn is prepared by the sol-gel method. Through materials composed of multiple elements such as cobalt, iron, manganese, copper, zinc, etc., combined with the photothermal effect, an efficient catalytic layer is formed to be used for the photothermal deodorization facilities of the garbage can.
It realizes efficient catalytic oxidation of H2S at room temperature, significantly reducing the dissipation of foul-odor gases in the trash can, and improving the environmental value and functionality of the trash can.
Smart Images

Figure CN119819319A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of malodorous gas purification, and in particular relates to a preparation method of a high entropy material and a product and application thereof. Background Art
[0002] Trash cans, also known as waste bins or trash cans, are containers for storing garbage. Most trash cans have lids to prevent the smell of garbage from spreading. The odor of trash cans is mainly caused by the corruption of organic waste and the decomposition of microorganisms. When garbage accumulates in trash cans, especially in a hot and humid environment, organic matter will quickly decay and release hydrogen sulfide (H2S), a foul-smelling gas with a strong pungent odor, which has an adverse impact on the surrounding environment and residents' lives.
[0003] In recent years, as people's requirements for quality of life continue to increase, some communities have adopted timed delivery, closed design, air purifiers and other methods to reduce the odor of garbage cans, but the above methods are difficult to achieve effective end-of-pipe treatment of H2S. Chemical washing and biological filtration are the main means of malodorous gas treatment at present. They have low operating costs and good deodorization effects, but there is a problem of inapplicability to application scenarios.
[0004] In order to control the emission of H2S from garbage cans, catalytic oxidation is an effective method. At present, in the field of H2S catalytic oxidation, metal oxide-based catalysts have better catalytic activity than carbon-based catalysts, but their low-temperature catalytic activity is weaker than that of carbon-based materials. Summary of the invention
[0005] In view of the above technical problems, the present invention proposes a preparation method of high entropy material and its product and application, so as to solve the problem that H2S odorous gas in existing garbage cans diffuses and pollutes the environment and affects people's physical and mental health.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the purposes of the present invention is to provide a method for preparing a high entropy material, comprising the following steps: using monohydrated citric acid as a chelating agent, ethanol and ethylene glycol as solvents, and using a cobalt source, an iron source, a manganese source, a copper source and a zinc source as raw materials, and synthesizing a high entropy material CoFeMnCuZn through a sol-gel method.
[0008] The sol-gel method can produce materials with high uniformity and fine structure. During the synthesis process, by controlling the formation of sol and gel, metal precursors with good dispersibility can be obtained, which is conducive to the formation of uniformly distributed metal nanoparticles during the subsequent heat treatment process. During the synthesis process, citric acid can form stable chelates with metal ions in cobalt, iron, manganese, copper and zinc sources, which helps to maintain the uniform distribution of metal ions in the solution, avoid precipitation and aggregation, and thus facilitate the formation of uniform sol and gel. Ethanol and ethylene glycol are solvents that can effectively dissolve metal organic compounds, and polyols such as ethylene glycol can also be used as chelating agents to further enhance the stability of metal ions. The high entropy material CoFeMnCuZn is composed of multiple elements, which can provide more active sites and enhanced electronic interactions, thereby improving the catalytic activity for H2S. The low-temperature activity may be due to the high specific surface area and porous structure of the material, which facilitates the adsorption and diffusion of H2S molecules. In summary, the synthesis of high-entropy material CoFeMnCuZn involves the use of chelating agents, the selection of solvents, the application of sol-gel method and the utilization of high-entropy effect. These factors work together to make the material show excellent catalytic activity, low-temperature activity and potential for multifunctional applications.
[0009] Furthermore, the molar ratio of the metal elements in the cobalt source, iron source, manganese source, copper source and zinc source is 4:1:1:1:1; wherein the cobalt source, iron source, manganese source, copper source and zinc source are all selected from nitrate, acetate or oxalate.
[0010] The high entropy material prepared by the present invention is composed of multiple elements in nearly equal molar ratios, and has excellent H2S catalytic activity, low-temperature activity and multifunctional applications.
[0011] Furthermore, the sol-gel method specifically comprises the following steps: mixing and stirring the raw materials, the chelating agent and the solvent to form a sol, and then drying, curing, grinding and calcining the sol.
[0012] Furthermore, the chelating agent is citric acid.
[0013] Further, the drying conditions are: drying at 80° C. for 9-12 hours; and / or
[0014] The curing conditions are: curing at 135°C for 10-12h; and / or
[0015] The calcination conditions are: heating to 450-500° C. at a heating rate of 3-5° C. / min, and calcining at this temperature for 3 hours.
[0016] A second object of the present invention is to provide a high entropy material prepared using the above preparation method.
[0017] The third object of the present invention is to provide a high-entropy photothermal catalytic layer made of the high-entropy material.
[0018] The fourth object of the present invention is to provide a method for preparing a high entropy photothermal catalytic layer, comprising the following steps: coating the high entropy material on a foam ceramic substrate, and preparing an integral catalyst by dip coating.
[0019] The fifth object of the present invention is to provide a photothermal deodorizing trash can, comprising a deodorizing shell and a trash can body, wherein the deodorizing shell is provided with a bottom plate, a catalytic component and a photothermal component in sequence from bottom to top;
[0020] The catalytic component is provided with a water-proof and breathable layer, a heat-insulating and breathable layer, an adsorption layer, a flame-retardant layer and the high-entropy photothermal catalytic layer in sequence from bottom to top;
[0021] The photothermal component provides heat to the catalytic component.
[0022] The excellent high entropy catalytic material of the present invention, combined with the transformation of garbage bin facilities and the photothermal effect, can promote the treatment of malodor problems in garbage bins.
[0023] Furthermore, the photothermal assembly includes at least one double-handled transparent top cover or double-handled Fresnel top cover sleeved on the upper part of the catalytic assembly;
[0024] The bottom plate is fastened to the photothermal assembly by nuts and bolts, and the catalytic assembly is placed in the middle space;
[0025] The bottom plate 3 is made of glass fiber reinforced plastic with a pore size of 10 meshes.
[0026] Compared with the prior art, the present invention has the following advantages and technical effects:
[0027] 1) The high entropy material prepared by the present invention adopts the sol-gel method and uses cobalt, iron, manganese, copper and zinc as metal elements, which has low raw material cost, simple method and is conducive to large-scale preparation;
[0028] 2) The high entropy material prepared by the present invention has excellent H2S catalytic activity at room temperature and can be applied to room temperature catalytic oxidation of H2S in practical scenarios;
[0029] 3) The present invention provides a photothermal deodorization facility for trash cans based on high entropy materials, which includes a catalytic component and a photothermal component that can efficiently decompose H2S odor. Combined with a stable bottom plate and a practical trash can body design, the functionality and environmental value of the trash can are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0031] Figure 1 The scanning electron microscope image and energy spectrum analysis image of the high entropy material CoFeMnCuZn prepared in Example 2 of the present invention;
[0032] Figure 2 This is an X-ray diffraction pattern of the high entropy material CoFeMnCuZn prepared in Example 2 of the present invention;
[0033] Figure 3 The H2S room temperature catalytic activity diagram of the high entropy material CoFeMnCuZn prepared in Example 2 of the present invention and the actual image of the CoFeMnCuZn powder;
[0034] Figure 4 It is a schematic diagram of the overall structure of the deodorization facility of the present invention;
[0035] Figure 5 It is a schematic diagram of the three-dimensional structure of the deodorization facility of the present invention;
[0036] Figure 6 This is a schematic diagram of the structure of the deodorizing housing of the present invention after the rotating module is removed;
[0037] Figure 7 This is the overall left rear view of the deodorization facility of the present invention;
[0038] Figures 4 to 7 In: 1-deodorizing shell, 2-trash can body, 3-bottom plate, 4-catalytic component, 5-photothermal component, 11-nuts, 12-bolts, 21-support module, 22-top extension module, 23-rotation module, 41-waterproof and breathable layer, 42-heat-insulating and breathable layer, 43-adsorption layer, 44-flame-retardant layer, 45-high-entropy photothermal catalytic layer. DETAILED DESCRIPTION
[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0040] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0044] The high entropy material provided in the embodiment of the present invention is prepared by a sol-gel method, comprising five elements of cobalt, iron, manganese, copper and zinc, the chelating agent is monohydrated citric acid, the solvent is ethanol and ethylene glycol, and the sol is stirred until it is stable and then dried, solidified, ground and calcined to finally obtain a high entropy material, which has excellent hydrogen sulfide catalytic activity at room temperature. Based on the high entropy material, the present invention designs a garbage can photothermal deodorization facility, including a deodorizing shell and a garbage can body, the deodorizing shell includes a bottom plate, a catalytic component, and a photothermal component, the bottom plate is fastened to the photothermal component, the hydrogen sulfide gas inside the garbage can diffuses through the bottom plate and the catalytic component, the catalytic component is sequentially provided with a water-proof and breathable layer, a heat-insulating and breathable layer, an adsorption layer, a flame-retardant layer, and a high-entropy photothermal catalytic layer from bottom to top, and the photothermal effect can be used to enhance the purification efficiency of the high entropy material. The present invention can effectively reduce the escape of hydrogen sulfide odor gas and solve the pollution problem of odor escape in garbage cans.
[0045] The preparation method of the high entropy material comprises the following steps: using monohydrated citric acid as a chelating agent, ethanol and ethylene glycol as solvents, and using a cobalt source, an iron source, a manganese source, a copper source and a zinc source as raw materials, and synthesizing the high entropy material CoFeMnCuZn through a sol-gel method.
[0046] In some embodiments, the molar ratio of the metal elements in the cobalt source, iron source, manganese source, copper source and zinc source is 4:1:1:1:1. The cobalt source, iron source, manganese source, copper source and zinc source are cobalt nitrate, iron nitrate, manganese nitrate, copper nitrate and zinc nitrate, respectively. In addition to nitrates, acetates or oxalates can also be selected, such as cobalt acetate, iron acetate, manganese acetate, copper acetate and zinc acetate; cobalt oxalate, iron oxalate, manganese oxalate, copper oxalate and zinc oxalate.
[0047] In some embodiments, the sol-gel method comprises the following specific steps: mixing a cobalt source, an iron source, a manganese source, a copper source and a zinc source, a chelating agent and a solvent to form a sol, and then drying, curing, grinding and calcining the sol.
[0048] In some embodiments, the drying condition is: drying at 80° C. for 9-12 hours. For example, in the following embodiments of the present invention, the drying condition can be selected to be drying at 80° C. for 9 hours or 12 hours.
[0049] In some embodiments, the curing condition is: curing at 135° C. for 10-12 hours. For example, in the following embodiments of the present invention, the curing can be selected to be curing at 135° C. for 10 hours or 12 hours.
[0050] In some embodiments, the calcination conditions are: heating to 450-500°C at a heating rate of 3-5°C / min, and calcining at this temperature for 3h. For example, in the following embodiments of the present invention, the heating rate can be selected as 3°C / min or 5°C / min; the calcination temperature can be selected as 450°C or 500°C. The high entropy material obtained by calcination has excellent H2S catalytic activity.
[0051] In some embodiments, the total mass of the cobalt source, iron source, manganese source, copper source and zinc source to the chelating agent and solvent is (2.926-14.743): (0.42-2.10) g: (101.11-205.46) mL.
[0052] High entropy materials can be prepared using the above preparation method.
[0053] A method for preparing a high entropy photothermal catalytic layer using a high entropy material comprises the following steps:
[0054] The high entropy material is dispersed in deionized water and stirred evenly, then aluminum sol is added and stirred continuously, and finally a nonionic surfactant (nonylphenol polyoxyethylene ether, NP-10) is added and stirred again to obtain a high entropy slurry after uniform dispersion;
[0055] Foam ceramic alumina 70*70*15 or silicon carbide 70*70*15 is selected as a carrier, and the high entropy slurry is coated on the carrier for multiple times and then dried to obtain a high entropy photothermal catalyst layer component.
[0056] In some embodiments, the ratio of the high entropy material, aluminum sol, deionized water and NP-10 is 100 g: 23.3 mL: 375 mL: 6 mL. The pore size of the foam ceramic carrier is 50 ppi.
[0057] Based on the problem of odor emission from trash cans, the embodiment of the present invention also provides a photothermal deodorizing trash can, which mainly integrates high entropy materials with the trash can and uses the photothermal effect to enhance the catalytic oxidation ability of hydrogen sulfide (H2S) of the high entropy materials. The specific structure includes: a deodorizing shell 1 and a trash can body 2, wherein the deodorizing shell 1 is provided with a bottom plate 3, a catalytic component 4 and a photothermal component 5 in sequence from bottom to top;
[0058] The catalytic component 4 is provided with a water-proof and breathable layer 41, a heat-insulating and breathable layer 42, an adsorption layer 43, a flame-retardant layer 44 and the high-entropy photothermal catalytic layer 45 in sequence from bottom to top;
[0059] The photothermal component 5 provides heat to the catalytic component 4 to promote the catalytic oxidation reaction of the malodorous gas and the desorption of the activated carbon.
[0060] The photothermal assembly 5 at least includes a double-handled transparent top cover or a double-handled Fresnel top cover sleeved on the upper part of the catalytic assembly 4, so as to allow the deodorizing shell 1 to be lifted as a whole and the material of the catalytic assembly 4 to be replaced.
[0061] The base plate 3 is fastened to the photothermal assembly 5 by nuts 11 and bolts 12, and the catalytic assembly 4 is placed in the middle space.
[0062] The bottom plate 3 is made of glass fiber reinforced plastic with a pore size of 10 meshes, so that H2S odorous gas can diffuse into the catalytic component 4 and is fixedly connected to the photothermal component 5. The internal material of the catalytic component 4 can be replaced by removing the fasteners and lifting the photothermal component 5 separately.
[0063] The photothermal component 5 can partially transmit or even concentrate sunlight to provide heat for the high-entropy photothermal catalytic layer 45 on the top layer of the catalytic component 4, which can improve the activity of the high-entropy material in catalytic oxidation of H2S on the one hand and provide desorption for the activated carbon adsorption layer on the other hand.
[0064] The trash can body 2 is different from a commercial outdoor environmentally friendly classified trash can. The top layer is partially retracted inside, which is called a support module (21) and is used to support the deodorizing shell 1 that is fastened thereto.
[0065] In some embodiments, the water-proof and breathable layer 41 may be made of polypropylene non-woven fabric or polyethylene breathable film to prevent water vapor and guide H2S malodorous gas into the heat-insulating and breathable layer 42; the heat-insulating and breathable layer may be made of silica aerogel to prevent the upper heat from transferring downward and guide H2S malodorous gas into the adsorption layer 43, the flame-retardant layer 44 and the high-entropy photothermal catalytic layer 45; the adsorption layer 43 may be made of high-iodine columnar activated carbon for adsorbing H2S; the flame-retardant layer 44 may be made of aluminum silicate ceramic material, which is disposed between the adsorption layer 43 and the high-entropy photothermal catalytic layer 45. The high-entropy photothermal catalytic layer 45 is made of the high-entropy material prepared by the present invention.
[0066] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0067] The raw materials used in the present invention are all purchased from the market.
[0068] The volume concentration of ethanol used in the following examples of the present invention is 20%, and the volume concentration of ethylene glycol used is 30%.
[0069] The technical solution of the present invention is further illustrated by the following embodiments.
[0070] Example 1
[0071] A method for preparing a high entropy material comprises the following steps:
[0072] (1) Weigh 1.456 g (5 mmol) of cobalt nitrate hexahydrate, 0.505 g (1.25 mmol) of iron nitrate nonahydrate, 0.314 g (1.25 mmol) of manganese nitrate tetrahydrate, 0.302 g (1.25 mmol) of copper nitrate trihydrate, and 0.349 g (1.17 mmol) of zinc nitrate hexahydrate into a beaker;
[0073] (2) Add 100 mL of ethanol to a beaker and stir for 30 min until evenly dispersed;
[0074] (3) Add 0.42 g of citric acid monohydrate powder to the beaker and stir. After the powder dissolves, stir for another 15 minutes.
[0075] (5) 1.11 mL of ethylene glycol was added to the beaker, stirred for 30 min, and then dried at 80 °C for 9 h and cured at 135 °C for 10 h to obtain a cured material;
[0076] (6) After the solidified material is fully ground into powder (15 min), it is transferred to a magnetic boat, the heating rate is set to 3 °C / min, and calcined at 450 °C for 3 h to obtain the high entropy material CoFeMnCuZn.
[0077] Example 2
[0078] A method for preparing a high entropy material comprises the following steps:
[0079] (1) Weigh 7.280 g of cobalt nitrate hexahydrate, 2.525 g of iron nitrate nonahydrate, 1.569 g of manganese nitrate tetrahydrate, 1.510 g of copper nitrate trihydrate, and 1.859 g of zinc nitrate hexahydrate into a beaker;
[0080] (2) Add 200 mL of ethanol to a beaker and stir for 30 min until evenly dispersed;
[0081] (3) Add 2.10 g of citric acid monohydrate powder to the beaker and stir. After the powder dissolves, stir for another 15 minutes.
[0082] (5) 5.46 mL of ethylene glycol was added to the beaker, stirred for 30 min, and then dried at 80 °C for 12 h and cured at 135 °C for 12 h to obtain a solidified material;
[0083] (6) After the solidified material is fully ground into powder (15 min), it is transferred to a crucible, the heating rate is set to 5 °C / min, and calcined at 500 °C for 3 h to obtain the high entropy material CoFeMnCuZn.
[0084] Figure 1 The scanning electron microscope image and energy spectrum analysis diagram of the high entropy material CoFeMnCuZn prepared in Example 2 of the present invention show that five metal elements, namely cobalt, iron, manganese, copper and zinc, are evenly distributed on the surface of the high entropy material.
[0085] Figure 2 This is the X-ray diffraction pattern of the high entropy material CoFeMnCuZn prepared in Example 2 of the present invention. It can be seen from the figure that the high entropy material has an obvious cobalt tetroxide characteristic peak, belongs to the spinel configuration, and has a high degree of crystallinity.
[0086] Application Example 1
[0087] The catalytic activity of high entropy material CoFeMnCuZn in hydrogen sulfide at room temperature was tested under the following conditions: total flow rate 165mL / min, total H2S content 40ppm, space velocity 99000h -1 , high entropy material CoFeMnCuZn powder 100 mg, 40 mesh tablets, the test temperature is room temperature.
[0088] Figure 3 The H2S room temperature catalytic activity diagram of the high entropy material CoFeMnCuZn prepared in Example 2 of the present invention and the actual picture of the CoFeMnCuZn powder are shown. It can be seen from the figure that the high entropy material has excellent H2S room temperature catalytic activity, and the H2S conversion rate can be maintained at more than 90% at room temperature and high space velocity for 700h.
[0089] Application Example 2
[0090] A method for preparing a high entropy photothermal catalytic layer comprises the following steps:
[0091] (1) 100 g of the high entropy material prepared in Example 2 was dispersed in 375 mL of deionized water and stirred for 30 min, then 23.3 mL of aluminum sol was added and stirred for 30 min, and finally 6 mL of NP-10 was added and stirred for 10 min to obtain a high entropy slurry;
[0092] (2) Foam ceramic alumina 70*70*15 was selected as a carrier (pore size of 50ppi), and the high entropy slurry was coated multiple times (the coating thickness reached 12μm. Although a thicker coating can provide better mechanical stability, it may also cause uneven coating thickness in the internal pores due to the increased thickness of the material) on the carrier and then dried to obtain a high entropy photothermal catalyst layer assembly.
[0093] A photothermal deodorizing trash can, such as Figure 4-Figure 7 As shown, the specific structure includes:
[0094] Deodorizing housing 1;
[0095] Trash can body 2;
[0096] The deodorizing shell 1 is provided with a base plate 3, a catalytic component 4 and a photothermal component 5 in sequence from bottom to top; the base plate 3 and the photothermal component 5 are fastened together as a whole by nuts 11 and bolts 12, and the catalytic component 4 is placed in the middle space; the base plate 3 is a glass fiber reinforced plastic with an aperture of 10 mesh, which has excellent corrosion resistance, and the pores are used for H2S malodorous gas to diffuse into the catalytic component 4, and is fixedly connected to the photothermal component 5. The internal material of the catalytic component 4 is replaced by lifting the photothermal component 5 separately after removing the fasteners; the photothermal component 5 is located at the uppermost layer of the deodorizing shell, and the photothermal component 5 can be opened and tightened by screwing the bolts 12 in a closed state. The photothermal component 5 can use the solar radiation energy to provide temperature to the inside, which can improve the H2S catalytic efficiency of the high entropy material on the one hand, and partially desorb the H2S adsorbed by the adsorption layer on the other hand to achieve cyclic purification;
[0097] The catalytic component 4 is provided with a waterproof breathable layer 41, a heat-insulating breathable layer 42, an adsorption layer 43, a flame-retardant layer 44 and the high-entropy photothermal catalytic layer 45 in sequence from bottom to top; the waterproof breathable layer 41 is tightly fitted with the bottom plate 3, and the heat-insulating breathable layer 42 is located above the waterproof breathable layer 41. The waterproof breathable layer 41 and the heat-insulating breathable layer 42 are used to allow the malodorous gas to pass through the adsorption layer 43 during operation while isolating the water vapor brought by the humidity inside the garbage can body 2 below from being transferred upward and the heat generated by the photothermal component 5 from being continuously transferred downward; the adsorption layer 43 adsorbs the odorous gas through the waterproof breathable layer 41, the heat-insulating breathable layer 4 2, and is used in combination with the high-entropy photothermal catalytic layer 45 to prevent H2S from escaping and improve the deodorization ability of the deodorization facility; the flame retardant layer 44 is located between the adsorption layer 43 and the high-entropy photothermal catalytic layer 45, and is used to prevent light from passing through the high-entropy photothermal catalytic layer and causing the adsorption layer 43 to ignite during operation; the high-entropy photothermal catalytic layer 45 is located at the uppermost layer of the catalytic component 4, and the catalyst in the high-entropy photothermal catalytic layer is the high-entropy material prepared by the present invention, and the photothermal effect is used to achieve efficient catalytic oxidation and removal of H2S odorous gas. The carrier pore size of 50ppi is conducive to increasing the active sites of the catalyst, prolonging the contact time between the H2S odorous gas and the catalyst, and improving the odorous gas purification rate.
[0098] The extension module 22 and the rotation module 23 are arranged on the top of the trash can body 2, which themselves support the deodorizing shell 1. In order to facilitate the replacement of the internal materials of the catalytic component 4 and further strengthen the support, the support module 21 retracted inwardly at the top layer of the trash can body 2 is used to support the fastened deodorizing shell 1. Except for the support module 21, the trash can body 2 is no different from a commercial outdoor environmentally friendly classified trash can and has universal applicability. Malodorous gases such as H2S are diffused inside the trash can body 2.
[0099] Due to the corruption of garbage inside the main body of the trash can, malodorous gases such as H2S will be produced. The gas diffusion will pass through the bottom plate, and then pass through the water-proof and breathable layer and the heat-insulating and breathable layer in turn to prevent moist water vapor from diffusing upward and affecting the catalytic effect, and the heat from continuously transferring downward and accelerating the diffusion of H2S malodorous gas inside the main body of the trash can. H2S is basically adsorbed by the adsorption layer in the form of dry gas, and the malodorous gas that is not adsorbed, saturated with adsorption or desorbed will further pass through the flame retardant layer and enter the high-entropy photothermal catalytic layer, and the odor will be purified through catalytic oxidation. Among them, the catalytic oxidation ability is weak in the state without sunlight, and the catalytic oxidation ability is high in the state with sunlight. Combined with the adsorption layer, it can play a role in deodorization and reduce the pollution of H2S malodorous gas to the environment.
[0100] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a high entropy material, characterized in that: The following steps are involved: The high entropy material CoFeMnCuZn is synthesized by a sol-gel method using monohydrated citric acid as a chelating agent, ethanol and ethylene glycol as solvents, and cobalt source, iron source, manganese source, copper source and zinc source as raw materials.
2. The method for preparing a high entropy material according to claim 1, characterized in that: The molar ratio of the metal elements in the cobalt source, iron source, manganese source, copper source and zinc source is 4:1:1:1:1; wherein the cobalt source, iron source, manganese source, copper source and zinc source are all selected from nitrate, acetate or oxalate.
3. The method for preparing a high entropy material according to claim 1, characterized in that: The specific steps of the sol-gel method include: mixing raw materials, chelating agents and solvents to form a sol, and then drying, solidifying, grinding and calcining the sol.
4. The method for preparing a high entropy material according to claim 3, characterized in that: The drying conditions are: drying at 80°C for 9-12h; and / or The curing conditions are: curing at 135°C for 10-12h; and / or The calcination conditions are: heating to 450-500° C. at a heating rate of 3-5° C. / min, and calcining at this temperature for 3 hours.
5. A high entropy material prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the high entropy material as claimed in claim 5 in the field of catalytic degradation of hydrogen sulfide.
7. A high entropy photothermal catalytic layer, characterized in that: Made of the high entropy material described in claim 5.
8. A method for preparing a high entropy photothermal catalytic layer as claimed in claim 7, characterized in that: The following steps are involved: The high entropy material is coated on a foam ceramic substrate to prepare a monolithic catalyst through dip coating.
9. A photothermal deodorizing trash can, comprising a deodorizing shell (1) and a trash can body (2), characterized in that: The deodorizing housing (1) is provided with a base plate (3), a catalytic component (4) and a photothermal component (5) in order from bottom to top; The catalytic component (4) is provided with a water-proof and breathable layer (41), a heat-insulating and breathable layer (42), an adsorption layer (43), a flame-retardant layer (44) and the high-entropy photothermal catalytic layer (45) according to claim 7 in sequence from bottom to top; The photothermal component (5) provides heat to the catalytic component (4).
10. The photothermal deodorizing trash can according to claim 9, characterized in that: The photothermal component (5) comprises at least one double-handled transparent top cover or double-handled Fresnel top cover sleeved on the upper part of the catalytic component (4); The base plate (3) is fastened to the photothermal assembly (5) by nuts (11) and bolts (12), and the catalytic assembly (4) is placed in the middle space; The bottom plate (3) is made of glass fiber reinforced plastic with a pore size of 10 meshes.
Citation Information
Patent Citations
Catalyst for catalytic combustion of organic volatile waste gas and preparation method thereof
CN113649022A
High-entropy perovskite catalyst, monolithic catalytic device and preparation method and application of monolithic catalytic device
CN117619422A
High-entropy oxide and preparation method and application thereof
CN118988338A
Garbage classification box deodorization device
CN218143548U
Catalyst for synergistic removal of nitrogen oxides and co, preparation method therefor and use
WO2024207996A1